The impact of nitrogen-doped reduced graphene oxide reinforcement on the thermal and mechanical properties of CFRP - Soyuguzel, Tahir; Kaftelen-Odabasi, Hulya; Mecitoglu, Zahit (Elsevier, 2024)
This study used experimental methods to investigate the impact of nitrogen-doped reduced graphene oxide particles (ND-RGOP) reinforcement on thermal and mechanical properties of unidirectional carbon fiber/ epoxy composites (CFRP). In the results, storage modulus and loss modulus significantly increase with the ND-RGOP addition. Besides, glass transition temperature is enhanced with the addition of 0.4 wt% ND-RGOP. In tensile mode, when compared to the baseline (0 weight% ND-RGOP) composites, the elastic modulus in the 0 degrees direction (E1) enhanced by 8.25 % and 11.39 % with 0.4 (0.4 weight%) and 0.8 (0.8 weight%) ND-RGOP addition, respectively. Besides, the ultimate tensile strength of the 0.4 ND-RGOP/CFRP composites significantly reduced by 16.33 % and 53.08 % in both 0 degrees and 90 degrees directions, respectively, as a result of the fracture mechanism changing from fiber pull out and fiber cracking to fiber breakage which was confirmed by SEM investigations. Furthermore, both the compressive modulus and the shear modulus increased with ND-RGOP reinforcement over 10 %, although the ultimate compressive strength decreases with low ND-RGOP reinforcement. In conclusion, low concentrations of ND-RGOP addition improves the thermal and mechanical properties of CFRP laminates in elastic region, although high concentrations of ND-RGOP decreases the thermal properties.
Keywords: Reduced graphene-oxide; Glass transition temperature; Fracture toughness; Compressive strength; Carbon fiber reinforced polymers